DAMPAK PANDEMI COVID-19 TERHADAP MANAJEMEN SEKOLAH MINGGU KOREA DI INDONESIA UNTUK PENGINTEGRASIAN PEMBELAJARAN IMAN [THE IMPACT OF THE COVID-19 PANDEMIC ON THE MANAGEMENT OF FAITH-LEARNING INTEGRATION OF KOREAN SUNDAY SCHOOL IN INDONESIA] - Choi, Chi Hyun; Purba, John Tampil; Sudibjo, Niko; Pramono, Rudy (JOHME: Journal of Holistic Mathematics Education, 2021)
This research is a case study that analyzes the problem of the Faith-Learning Integration management process for the Korean Sunday School “Y” in Indonesia during the COVID-19 pandemic. In this research, data collection was carried out with 5 informants, 58 questionnaires from respondents consisting of students, parents and teachers as well as recordings of student activity results. From the results of this study, it can be seen that there are several obstacles experienced by students, teachers and parents in the Faith-Learning Integration management process. First, students are not satisfied with centering on video learning platforms because there is no interaction between teachers, students and their friends so it needs to be changed from a one-way platform, such as video to an interactive platform between students and teachers such as Zoom or Google Classroom, etc.  In addition, students from parents of other religions do not get support and attention from their parents to carry out  Faith-Learning Integration with Work From Home (WFH)  so that  Faith-Learning Integration activities stop. Second, teachers' technical skills are very limited, so interactive online classroom training is required. Third, parents feel burdened and stressed when they have to give examples of faith, morals and good discipline to children in  Faith-Learning Integration during WFH. The last obstacle, the 5 dimensions of the Faith-Learning Integration are not tightly integrated with each other so they do not run in harmony. The dimensions of Leitourgia and Didache were implemented well, while Kerygma, Koinonia, and Diakonia were not carried out well due to social distancing obstacles. For this reason, it is recommended that "Y" management use an interactive platform and develop innovative and creative ways that can motivate students so that they do not feel the distance between teachers and students and the surrounding environment is getting farther away even though they participate in social distancing.BAHASA INDONESIA ABSTRACT: Penelitian ini adalah studi kasus yang menganalisa masalah proses manajemen pengintegrasian pembelajaran iman Sekolah Minggu Korea “Y” di Indonesia pada masa pandemi COVID-19. Dalam penelitian ini dilaksanakan pengumpulan data dengan 5 orang narasumber, 58 hasil kuesioner dari responden yang terdiri dari siswa, orangtua dan guru serta rekaman hasil aktivitas siswa. Dari hasil penelitian ini terlihat adanya beberapa kendala yang dialami oleh siswa, guru dan orang tua dalam proses manajemen pengintegrasian pembelajaran iman. Pertama, siswa tidak puas dengan berpusat pada media pembelajaran video karena tidak terjadi interaksi antara guru, siswa dan teman-temannya sehingga perlu diubah dari media yang bersifat satu arah, seperti video ke berbagai media yang interaktif antara siswa dan guru seperti Zoom atau Google Classroom, dll. Selain itu, siswa dari orangtua yang beragama lain kurang mendapat dukungan dan perhatian dari orangtuanya untuk melakukan pengintegrasian pembelajaran iman dengan pembelajaran daring dari rumah sehingga aktivitas pengintegrasian pembelajaran iman jadi terhenti. Kedua, keterampilan teknis guru sangat terbatas sehingga diperlukan pelatihan kelas online secara interaktif. Ketiga, orangtua merasa terbebani dan stress ketika harus memberikan contoh iman, moral dan disiplin yang baik kepada anak-anak dalam pengintegrasian pembelajaran iman selama pembelajaran daring dari rumah. Kendala yang terakhir, 5 dimensi dari pengintegrasian pembelajaran iman tidak terintegrasi satu sama lain secara erat sehingga tidak berjalan selaras. Dimensi Leitourgia dan Didache dilaksanakan dengan baik, sedangkan Kerygma, Koinonia, dan Diakonia tidak terlaksana dengan baik karena adanya hambatan social distancing. Untuk itu disarankan manajemen “Y” menggunakan berbagai media yang interaktif dan mengembangkan cara yang inovatif dan kreatif yang dapat memotivasi siswa supaya tidak merasakan jarak antara guru dan siswa serta lingkungan sekitarnya semakin jauh walaupun mengikuti social distancing.